Pengaruh Profitabilitas, Debt Default, dan Reputasi KAP terhadap Opini Audit Going Concern: Studi Empiris pada Perusahaan Properti dan Real Estate yang Terdaftar di BEI Tahun 2019-2022 - Friska Meilani Ikrar; Halmawati Halmawati (Jurnal Eksplorasi Akuntansi, 2024)
This study aims to provide empirical evidence regarding the effect of pprofitability, debt default, and audit reputation on going concern audit opinion. This research uses a quantitative approach with the type of causal research. The population in this study are companies in the property and real estate sectors that have been listed on the Indonesia Stock Exchange (IDX) in 2019-2022. By using purposive sampling method obtained 192 samples. Profitability is measured by Return on Asset. Debt default is measured by dummy variables. Audit reputation is measured by dummy variables, and going concern audit opinion is measured using dummy variables. This study uses logistic regression analysis to test the proposed hypothesis. The research results show that profitability has a negative effect on going concern audit opinion, debt default and audit reputation have a significant effect on going concern audit opinion.